Automated complex for thermistors calibration and measurement of their parameters - Andreev, A.N.; Andreeva, O.N.; Lazarenko, A.G. (Radiotekhnika, 2018)
The article describes in details a principle and operating modes of automated measuring system based on the Arduino platform, designed to study the temperature dependence of thermistors electrical resistance and to determine their parameters: the temperature coefficient of resistance in the temperature range T = (265 – 355) K and the time constant characterizing thermal inertness of the thermistor. Some testing results of the developed complex were presented and, using the Levenberg – Marquardt algorithm, the thermistor was calibrated – coefficients entering Steinhart – Hart equation were calculated.